Availability and Performance Analysis of Primary Treatment Unit of Sewage Plant - Saini, Monika; Goyal , Drishty; Kumar, Ashish (Thailand Statistician, 2023)
The main objective of present study is to analyze availability and performance of primary treatment unit of sewage plant (STP) with component wise redundancy. For this purpose, a novel mathematical model for availability and performance analysis of primary unit of sewage treatment plant has been proposed introducing the concept of redundancy and constant failure rates. Primary unit of sewage treatment system is a serial process system in which five subsystems comprises in series structure. The system has been analyzed using Markov birth-death process, Chapman-Kolmogorov differential equation and supplementary variable technique. All the repair rates considered as arbitrarily distributed. The needful data has been taken with the help of the maintenance personnel of the plant. Numerical and graphical results of the study have been appended for a particular case and the results also shared with the plant personnel.